2022
DOI: 10.1016/j.gastha.2021.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence and Machine Learning: What You Always Wanted to Know but Were Afraid to Ask

Abstract: The access to increasing volumes of scientific and clinical data, particularly with the implementation of electronic health records, has reignited an enthusiasm for artificial intelligence and its application to the health sciences. This interest has reached a crescendo in the past few years with the development of several machine learning-and deep learning-based medical technologies. The impact on research and clinical practice within gastroenterology and hepatology has already been significant, but the near … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…These are common issues encountered in the development of models using AI techniques, particularly in ML. Hence, understanding these concepts is vital for developing effective and reliable AI-based models (Rattan et al, 2022). Overfitting and underfitting issues could be overcome by data augmentation, regularization, adjustment of the model, and k-fold crossvalidation methods (Mutasa et al, 2020).…”
Section: Overfitting and Underfittingmentioning
confidence: 99%
“…These are common issues encountered in the development of models using AI techniques, particularly in ML. Hence, understanding these concepts is vital for developing effective and reliable AI-based models (Rattan et al, 2022). Overfitting and underfitting issues could be overcome by data augmentation, regularization, adjustment of the model, and k-fold crossvalidation methods (Mutasa et al, 2020).…”
Section: Overfitting and Underfittingmentioning
confidence: 99%
“…Doctors won't likely be replaced by AI, as has lately been suggested in the literature, 29,30 because smart medical technologies already exist to assist clinicians in better patient management. Nonetheless, as recent studies have shown 1,10 comparisons between artificial intelligence solutions and doctors regularly take place, as if the two counterparts, were in competition. Figure 4 show the Insilico Analysis of Bioinformatics Future research should compare doctors who use artificial intelligence apps versus doctors who don't, and should include translational clinical trials in those comparisons.…”
Section: Will Ai Replace Doctors In the Medical Field?mentioning
confidence: 99%
“…6 These AI-based "expert systems" were hampered by rigid, rule-based structures, which prevented them from being generalizable, preventing widespread acceptance and causing a split between the areas of AI and medicine until the turn of the century when various applications of AI were projected for the human welfare. [7][8][9][10] The term "Medical Technology and Biomedical Engineering" is frequently used to refer to a variety of instruments that can help medical practitioners diagnose patients earlier, prevent problems, optimize therapy and/or offer less intrusive options, and shortens hospital stays for patients and society as a whole. 11 Prior to the advent of smart phones, wearable's, sensors, and communication systems, medical technologies were primarily known as traditional medical devices (such as prosthetics, stents, and implants).…”
Section: Introductionmentioning
confidence: 99%
“…Por último, se realizó el entrenamiento del modelo de ML utilizando el 80% de los datos y mediante el 20% de los datos restantes se comprueba el modelo, se selecciona esta distribución con base al principio de Pareto [26]. La calidad de los modelos de regresión lineal se evaluó mediante el coeficiente de determinación (R2) y el error-cuadrático-medio (MSe) para calibración y validación [27]. La Fig.…”
Section: B Descripción Del Modelounclassified